2017
DOI: 10.1038/ejhg.2017.112
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the COX4I1 gene is associated with short stature, poor weight gain and increased chromosomal breaks, simulating Fanconi anemia

Abstract: We describe a novel autosomal recessive form of mitochondrial disease in a child with short stature, poor weight gain, and mild dysmorphic features with highly suspected Fanconi anemia due to a mutation in COX4I1 gene. Whole Exome Sequencing was performed then followed by Sanger confirmation, identified a K101N mutation in COX4I1, segregating with the disease. This nuclear gene encodes the common isoform of cytochrome c oxidase (COX) subunit 4 (COX 4-1), an integral regulatory part of COX (respiratory chain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Mutation in the human COX4I1 gene induces short stature, poor weight gain, and chromosomal breaks (Abu‐Libdeh et al, ). Furthermore, low COX4I1 expression is associated with impaired ATP production and elevated ROS (Abu‐Libdeh et al, ). A recent study has indicated that a COX4I1‐HSP70 complex contributes to the formation of COX, leading to the maintenance of the mitochondrial membrane potential (Bottinger et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutation in the human COX4I1 gene induces short stature, poor weight gain, and chromosomal breaks (Abu‐Libdeh et al, ). Furthermore, low COX4I1 expression is associated with impaired ATP production and elevated ROS (Abu‐Libdeh et al, ). A recent study has indicated that a COX4I1‐HSP70 complex contributes to the formation of COX, leading to the maintenance of the mitochondrial membrane potential (Bottinger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study has shown that the defective production of COX causes myopathy and Leigh syndrome (Pillai et al, 2019). Mutation in the human COX4I1 gene induces short stature, poor weight gain, and chromosomal breaks (Abu-Libdeh et al, 2017). Furthermore, low COX4I1 expression is associated with impaired ATP production and elevated ROS (Abu-Libdeh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, NAC and ascorbate were shown to decrease ROS production in fibroblasts with a mutation in COX4‐1 subunit [46].…”
Section: Generalist Strategiesmentioning
confidence: 99%
“…Biallelic variants in COX4I1 (OMIM: 123864) have been previously described in a patient who presented with short stature, poor weight gain, dysmorphic features and features of Fanconi anemia (Abu‐Libdeh et al, ). COX4I1 , located at 16q24.1, encodes the subunit IV isoform 1, the principal isoform for COX‐IV subunit of cytochrome c oxidase (COX) or complex IV in human beings and other vertebrates.…”
Section: Introductionmentioning
confidence: 99%